1999
DOI: 10.3402/tellusa.v51i5.14471
|View full text |Cite
|
Sign up to set email alerts
|

Flow response to large-scale topography: the Greenland tip jet

Abstract: Numerical model simulations of idealized and observed flows are used to investigate the dynamics of low-level jet streams that form in stratified flow downstream of the vertex of large elliptical barriers such as the southern tip of Greenland, hereafter referred to as ''tip jets''. The tip jet dynamics are governed by conservation of Bernouli function as parcels accelerate down the pressure gradient during orographic descent. In some circumstances, the Greenland tip jet is influenced by baroclinic effects such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
155
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(163 citation statements)
references
References 41 publications
8
155
0
Order By: Relevance
“…The reason for this climatological accolade is the frequent low-level 'tip jets' that occur there as a result of interactions between the synoptic-scale flow and the high topography of Greenland. Westerly tip jets were first investigated, through numerical model simulations, by Doyle and Shapiro (1999), while easterly or reverse tip jets were first investigated by Moore (2003) and Moore and Renfrew (2005). Doyle and Shapiro suggested tip jets were driven by a Bernoulli acceleration as flow descended down the lee side of Greenland, as well as acceleration in the lee due to flow distortion around the tip of Greenland.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this climatological accolade is the frequent low-level 'tip jets' that occur there as a result of interactions between the synoptic-scale flow and the high topography of Greenland. Westerly tip jets were first investigated, through numerical model simulations, by Doyle and Shapiro (1999), while easterly or reverse tip jets were first investigated by Moore (2003) and Moore and Renfrew (2005). Doyle and Shapiro suggested tip jets were driven by a Bernoulli acceleration as flow descended down the lee side of Greenland, as well as acceleration in the lee due to flow distortion around the tip of Greenland.…”
Section: Introductionmentioning
confidence: 99%
“…Almost all previous studies have relied exclusively on either satellite-based observations, such as scatterometer winds (e.g. QuikSCAT winds: Moore and Renfrew, 2005;Sampe and Xie, 2007), meteorological analyses or reanalyses (Moore, 2003;Egger, 2006), or numerical weather prediction (NWP) simulations (Doyle and Shapiro, 1999;Petersen et al, 2003Petersen et al, , 2005Orr et al, 2005;Martin and Moore, 2007;Ohigashi and Moore, 2009). The only exceptions are two recent studies that jets'; here we use the adjective 'easterly' in preference to 'reverse' tip jet.…”
Section: Introductionmentioning
confidence: 99%
“…Greenland itself likely plays a crucial role in forcing the cross-coastal flows, as previous studies have found that the interaction of the large-scale atmosphere with the high topography (shown in Figure 1-1a) creates strong wind events, particularly near the east coast [Moore, 2003]. These include tip jets around the southern tip of Greenland [Doyle and Shapiro, 1999, Våge et al, 2009, Moore and Renfrew, 2005, Renfrew et al, 2009a, Outten et al, 2009 and barrier winds at different locations along the east coast [Moore and Renfrew, 2005, Harden et al, 2011, Harden and Renfrew, 2012, Moore, 2012, and it was found that both types of wind events are associated with deep cyclones. In fact, the regions off the southwest, southeast and east Greenland coast are characterized by a particularly high cyclone frequency and large deepening rates [Zhang et al, 2004, Tsukernik et al, 2007.…”
Section: Introductionmentioning
confidence: 92%
“…The interaction of synoptic weather systems with the high topography can result in intense wind events, particularly around southern Greenland, which is one of the windiest regions in the World Ocean [Sampe and Xie, 2007]. Among these wind events are tip jets around the southern tip of Greenland [Doyle and Shapiro, 1999, Våge et al, 2009, Moore and Renfrew, 2005, Renfrew et al, 2009a, Outten et al, 2009, barrier winds at different locations along the east coast [Moore and Renfrew, 2005, Harden et al, 2011, Harden and Renfrew, 2012, Moore, 2012 and plateau jets along the eastern and western margin of the ice sheet [Moore et al, 2013]. Observations indicate the existence of another type of wind event associated with a strong downslope flow across Greenland's southeast coast Heinemann, 2002, Mills andAnderson, 2003], but to date there has been no comprehensive study about this type of wind event, and winds across Greenland's coast, either onshore or offshore, have generally received very limited attention.…”
mentioning
confidence: 99%
“…Two mechanisms generating the tip jet have been proposed: The first involves orographic descent. Doyle and Shapiro (1999) argued that the tip jets are governed by conservation of the Bernoulli function when air parcels descend sharply down the lee slope of Greenland (the Bernoulli function is the sum of enthalpy, kinetic energy, and potential energy per unit mass; Schär, 1993). The second mechanism, also noted by Doyle and Shapiro (1999) and later expanded upon by Moore and Renfrew (2005), involves blocking due to the high topography of Greenland.…”
Section: Introductionmentioning
confidence: 99%